MEXICAN PEASANTS AND THE WAR OF INDEPENDENCE: A TOUR (Tzintzun, Revista de Estudios Históricos, 2016)
This article reviews the historiography from 1980 on the peasant participation inthe armed movements in the rural areas of the New Spain between 1810 and 1821.It also tries to explain the origins of the new interest in the subject that arose in thedecade of the 1980 and because the English-speaker historians were more interestedin the subject than their Mexican colleagues. It pays attention in the importance ofthe social history of the colony, the international influence of debates on thepeasants movements which originated themselves in the North American adventurein Vietnam, and the English-speaker fascination with the so call new culturalhistory. It reviews a series of contributions done by historians of several countrieson the peasants’ attitude during the Mexican insurgency, including works ofTutino, Hamnett, Van Young, Guardino, Escobar Ohmstede, Ortiz Escamilla,Ducey, Guedea and Landavazo. It also describes some advances in compatibleareas like new works on the insurgent leadership and the insurgent speech. Itfinishes with some opinions on the possibilities of advancing our knowledge of thereasons for the participation farmer in the war of independence.
Keywords: Independence of Mexico; peasants´ movements; social and cultural history; analysis of historiography